Measurements of rhenium isotopic composition in low-abundance samples. Issue 2 (7th January 2020) - Dellinger, Mathieu; Hilton, Robert G.; Nowell, Geoffrey M.
Abstract : A new method is presented for measuring accurate stable rhenium isotopic ratios (δ 187 Re, in ‰) by MC ICP-MS Neptune by using 10 13 Ω amplifiers and pre-concentration of Re from water samples in the field. Abstract : Rhenium (Re) is a trace element whose redox chemistry makes it an ideal candidate to trace a range of geochemical processes. In particular, fractionation of its isotopes 187 Re (62.6% abundance) and 185 Re (37.4%) may be used to improve our understanding of redox reactions during weathering, both in the modern day and in geological archives. Published methods for measurement of Re isotopic composition are limited by the requirements of Re mass to reach a desirable precision, making the analysis of many geological materials unfeasible at present. Here we develop new methods which allow us to measure Re isotope ratios (reported as δ 187 Re) with improved precision: ±0.10‰ (2 σ ) for a mass of Re of ∼1 ng to ±0.03‰ (2 σ ) for a mass of Re of >10 ng. This is possible due to the combination of a modified column chemistry procedure and the use of 10 13 Ω amplifiers for measurement via multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS). For river water samples (with Re concentrations typically ∼10 −12 g g −1 ) we design a field-based pre-concentration of Re that can be used with large volumes of filtered water (5–20 L) shortly after sample collection to provide abundant Re for isotope analysis. As a result of these developments we provide new measurements of δ 187 Re in standards reference materials (δ 187 Re values range from −0.06 ± 0.07‰ to +0.19 ± 0.05‰) and a seawater standard (δ 187 Re = +0.10 ± 0.04‰), providing impetus for further exploration of the Re isotope system.